Comparison of the effectiveness of robusta coffee bean extract and arabica coffee bean extract on the growth of Candida albicans - Adriana, Shirley; Pinem, Pinta Malem; Watri, Desi (Buletin Kedokteran & Kesehatan Prima, 2025)
Oral thrush, a fungal infection often associated with inadequate oral hygiene, necessitates treatment with antimicrobial agents. Extracts from Coffea canephora (Robusta) and Coffea arabica L. (Arabica) coffee beans contain bioactive compounds that demonstrate inhibitory activity against Candida albicans. This study investigated the comparative inhibitory efficacy of Robusta and Arabica coffee bean extracts on Candida albicans growth. A randomised, post-test only control group design was employed in this experimental laboratory study. Twelve treatment groups were established, and the disc diffusion method was used to assess antibacterial activity. Inhibition diameters were measured using a vernier caliper. Statistical analysis was performed using the Kruskal-Wallis and Mann-Whitney tests. The mean inhibition diameters for Robusta coffee bean extract (Coffea canephora) were as follows: 9.28 ± 2.585 mm at 12.5% concentration, 12.35 ± 0.050 mm at 25%, 14.55 ± 0.050 mm at 50%, 16.50 ± 0.477 mm at 75%, and 18.55 ± 0.477 mm at 100%. For Arabica coffee bean extract (Coffea arabica L.), the mean inhibition diameters against Candida albicans were 8.10 ± 1.117 mm at 25% concentration, 10.91 ± 1.188 mm at 50%, 15.61 ± 2.115 mm at 75%, and 16.71 ± 1.980 mm at 100%. The positive control exhibited a mean inhibition diameter of 15.85 ± 0.180 mm. No inhibition was observed for Arabica coffee bean extract at 12.5% concentration or the negative control. The results indicate that Robusta coffee bean extract demonstrated a significantly greater inhibitory effect on Candida albicans growth compared to Arabica coffee bean extract. Liquid chromatography-mass spectrometry (LC-MS) analysis of both Robusta and Arabica coffee bean extracts revealed the presence of caffeine and chlorogenic acid, which likely contribute to their observed inhibitory activity.